Readiness For The Exam - Fitria Susanti; Daharnis Daharnis (Universitas Negeri Padang, 2019)
To find out the achievement of educational goals need to be tested. To face the exam students need to do a variety of readiness both (1) physical readiness (2) psychological readiness (3) readiness of stationery and exam materials. This research uses quantitative descriptive methods. The population of this study was all students of SMP Negeri 13 Padang, totaling 848 students and the sample in the study were students of class VII, VIII and IX at SMP Negeri 13 Padang, totaling 272 students who were selected using the Simple Random Sampling technique. Data collection tools used in the form of instruments (questionnaire) and data analysis using descriptive methods. The findings of the study revealed that overall the readiness of students facing exams was in the good category, which was detailed as follows, (1) students' psychological readiness to take exams was classified as very good, while (2) physical readiness, stationery and student's exam materials to face exams quite good.